The Role of Environmental Easement Rights in Building Environmental, Social, and Governance (ESG) Principles - Erwin Syahruddin; Sugeng Sugeng; Yaoping Liu (Universitas Lampung, 2025)
This article critically explores the potential of environmental use rights as a legal mechanism to advance a more inclusive and sustainable Environmental, Social, and Governance (ESG) framework. Traditionally limited to physical access or utility purposes, use rights have yet to realize their ecological and social functions within environmental governance. Using a normative legal and conceptual approach, this study argues that environmental use rights can enhance landowner accountability for ecological integrity while institutionalizing ESG principles of stewardship, transparency, and responsibility. Positioned as a hybrid construct between private property rights and public environmental interests, these rights offer a transformative legal pathway toward ecological justice and participatory land governance. Recognizing their normative and ecological value can empower communities to monitor land use, mitigate spatial conflicts, and embed environmental considerations into ESG assessment structures.